Evaluation of oxidative stress level: reactive oxygen species, reduced glutathione, and D-dimer in patients hospitalized due to COVID-19 - Claudionei Roessler; Karen Cristine Silva de Oliveira; Auricélia Xavier de Oliveira Portella; Paulo Cezar Nunes Fortes; Franciéle Romero Machado; Stífani Machado Araujo; Marina Prigol; Léia Carolina Lucio; Dalila Moter Benvegnú; Lirane Elize Defante Ferreto (Taylor & Francis Group, 2023)
ABSTRACTElevated D-dimer levels at hospital admission may also indicate a higher likelihood of progressing to a severe or critical state. This study aimed to assess reactive oxygen species (ROS), non-enzymatic antioxidant reduced glutathione (GSH), and D-dimer levels in COVID-19 patients upon admission, examining their association with mortality outcomes. Data was collected from the medical records of 170 patients hospitalized in a referral hospital unit between March 2020 and December 2021. Patients were divided into two groups: the ward bed group (n = 87), comprising 51% with moderate clinical conditions, and the intensive care unit (ICU) group (n = 83), comprising 49% with severe conditions. The mean age was 59.4 years, with a male predominance of 52.4%. The overall death rate was 43%, with 30.6% in the moderate group and 69.4% in the severe group. The average time from symptom onset to hospitalization was 6.42 days. Results showed that non-survivors had high D-dimer and ROS counts, longer ICU stays, and worse saturation levels at admission. In conclusion, elevated ROS and D-dimer levels may contribute to worse outcomes in critically ill patients, potentially serving as specific and sensitive predictors of poor outcomes upon admission.